Early life nociceptive stimulus and fentanyl exposure increase hippocampal neurogenesis and anxiety but do not affect spatial learning and memory - Rêgo, Debora da Silva Bandeira; Silva, Clivandir S.; Mello, Luiz Eugenio A. M.; Leslie, Ana Teresa Figueiredo Stochero (Frontiers in Neuroscience, 2022)
This study aimed to determine whether preemptive fentanyl administration in neonatal rats reduces the impact of a nociceptive stimulus initiated during the first day of life (P1) on hippocampal neurogenesis, behavior, and learning. At P1, Wistar rat pups received either a subcutaneous injection of fentanyl (F) before intraplantar injection of complete Freund’s adjuvant (CFA) (CFA+F group), an isolated injection of CFA (CFA group), or subcutaneous injection of fentanyl without CFA injection (F). Control animals received saline injections using the same route and volume as the treatment groups. Hippocampal neurogenesis was evaluated by 5′-bromo-2′-deoxyuridine (BrdU) staining on P10 and P39 to assess neuronal proliferation and survival, respectively. Anxiety behavior in adulthood was assessed using an open field test (OF) and an elevated plus maze test (EPM). Spatial memory was assessed on a Morris water maze test (MWM), where the animals were trained for seven days, beginning on P81, and the probe trial was performed to evaluate memory retention. Although the CFA+F group showed an increased number of proliferative cells on P10, this finding did not persist on P39. The CFA+F group spent more time in the closed arms in the EPM, revealing more anxious behavior, although the early noxious experience, both with and without fentanyl, did not alter neurogenesis in adolescence and learning in adulthood. This study highlights that the impact of pain in early life pain combined with fentanyl on hippocampal neurogenesis on P10 did not persist on P39. In addition, this combined intervention during the first week of life was associated with higher anxiety levels.